KOMUNIKASI ANTAR KARYAWAN ETNIS JAWA DAN TIONGHOA - Ferdika Tedjakusuma; Eddy Madiono Sutanto (Jurnal Manajemen dan Kewirausahaan, 2015)
This study was to describe the horizontal communication among employees with ethnic diversity in communication process, barriers of communication as well as efforts made by the employees in resolving horizontal communication conflicts. Data collection technique used focus group discussion of structured interviews to three Javanese employees and three Chinese employees. The interviews were done by dividing the employees into two discussion groups according to their ethnics to answer the same research questions. The implications of this study were in accordance with the results of the research which stated that employees' ethnic diversity didn’t directly affect the continuity of horizontal communication among employees in the organization.